Pengembangan Media Animasi Berbasis Sparkol Videoscribe pada Materi Pembuatan Pola Celana Pria di Smk Negeri 1 Batu - Nila Kusumaningtyas; Nur Endah Purwaningsih; Hapsari Kusumawardani (Universitas Ngeri Malang, 2021)
This study aims to develop animation media based on Sparkol Video Scribe on the material making patterns of men's pants at 1 Batu Vocational High School. This is related to the development of technology, so that there is a need for new computer-based media that are more interactive to support the learning process The method used in this research is development research with ADDIE models. Stages of development carried out include: (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. The research subjects in this development research were class XII students of the Boutique Clothing Department at 1 Batu Vocational High School totaling 26 students. The developed media contains learning objectives and competencies, the understanding of men's pants and men's pants patterns, sizes, and animated video tutorials for making men's pants patterns. The feasibility of the media that has been made is tested on material experts, media experts and linguists, after being repaired and declared feasible then proceed to the implementation phase of the XII grade students of the Boutique Clothing Department at 1 Batu Vocational High School. The results of expert validation and field trials state that learning media that have been developed are suitable for use with the following results: material expert validation was 92.7 percent, media expert validation was 97.2 percent, language expert validation was 97.5 percent. Data from the field trial results was 92.74 percent. Based on these results it can be concluded that the developed animation media is suitable as a learning media. The media developed are clear, easy to understand and easy to operate, an attractive media display can motivate and attract students to learn because the media can be used as a means of independent learning. Suggestions for further researchers should be the duration in the video tutorial for making men's pants patterns slowed down so that students find it easier to follow the stages of learning.